Presenilin 1 is necessary for neuronal, but not glial, EGFR expression and neuroprotection via γ‐secretase‐independent transcriptional mechanisms. Issue 9 (18th May 2015) - Bruban, Julien; Voloudakis, Georgios; Huang, Qian; Kajiwara, Yuji; Rahim, Md Al; Yoon, Yonejung; Shioi, Junichi; Sosa, Miguel A. Gama; Shao, Zhiping; Georgakopoulos, Anastasios; Robakis, Nikolaos K.
ABSTRACT: Epidermal growth factor receptor (EGFR) plays pivotal roles in cell proliferation, differentiation, and tissue development, while EGFs protect neurons from toxic insults by binding EGFR and stimulating survival signaling. Furthermore, recent evidence implicates this receptor in neurometabolic disorders like Alzheimer disease and aging. Here we show that absence of presenilin 1 (PS1) results in dramatic decrease (>95%) of neuronal EGFR and that PS1‐null (PS1 ‐/‐ ) brains have reduced amounts of this receptor. PS1 ‐/‐ cortical neurons contain little EGFR and show no epidermal growth factor‐induced survival signaling or protection against excitotoxicity, but exogenous EGFR rescues both functions even in absence of PS1. EGFR mRNA is greatly reduced (>95%) in PS1 ‐/‐ neurons, and PS1 ‐/‐ brains contain decreased amounts of this mRNA, although PS1 affects the stability of neither EGFR nor its mRNA. Exogenous PS1 increases neuronal EGFR mRNA, while down‐regulation of PS1 decreases this mRNA. These effects are neuron specific, as PS1 affects the EGFR of neither glial nor fibroblast cells. In addition, PS1 controls EGFR through novel mechanisms shared with neither γ‐secretase nor PS2. Our data reveal that PS1 functions as a positive transcriptional regulator of neuronal EGFR controlling its expression in a cell‐specific manner. Severe downregulation of EGFR may contribute to developmental abnormalities and lethal phenotype found in PS1, but not PS2, null mice. Furthermore, PS1 may affect neuroprotection and Alzheimer disease by controlling survival signaling of neuronal EGFR.—Bruban, J., Voloudakis, G., Huang, Q., Kajiwara, Y., Al Rahim, M., Yoon, Y., Shioi, J., Gama Sosa, M. A., Shao, Z., Georgakopoulos, A., Robakis, N. K. Presenilin 1 is necessary for neuronal, but not glial, EGFR expression and neuroprotection via 7‐secretase‐independent transcriptional mechanisms. FASEB J. 29, 3702‐3712 (2015). www.fasebj.org